UJI CEMARAN MIKROBA SUSU KEDELAI DI WILAYAH BANJARMASIN UTARA DENGAN METODE ANGKA LEMPENG TOTAL - Wibowo, Joko Priyanto; Hakim, Khoirul Usmanul; Mirajunnisa (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
The microbial contamination of soymilk is possibly due to the improper production process. Soymilk product must pass the safety and quality assessment prior to distribution as a commercial product. The research was conducted to determine the level of microbial contamination in soymilk product that are distributed by street vendors in North Banjarmasin. The Total Plate Count (TPC) method was performed to five samples of soymilk to determine the level of microbial contamination. The Total Plate Count (TPC) number of the samples as follow: SG (22,000 ± 2,500 CFU/mL), CU (27,667 ± 2,363 CFU/mL), SA (12,667 ± 1,268 CFU/mL), SM (18,667 ± 1,528 CFU/mL), and KU (18,500 ± 1,323 CFU/mL). In conclusion, all samples of soymilk product North Banjarmasin meet the standard criteria of the Badan Standarisasi Nasional (BSN), which is the TPC less than 1×106 CFU/mL.